2011
DOI: 10.1088/2041-8205/741/1/l9
|View full text |Cite
|
Sign up to set email alerts
|

On Water Formation in the Interstellar Medium: Laboratory Study of the O+d Reaction on Surfaces

Abstract: In the interstellar medium (ISM), an important channel of water formation is the reaction of atoms on the surface of dust grains. Here, we report on a laboratory study of the formation of water via the O+D reaction network. While prior studies were done on ices, as appropriate to the formation of water in dense clouds, we explored how water formation occurs on bare surfaces, i.e., in conditions mimicking the transition from diffuse to dense clouds (Av ∼ 1-5). Reaction products were detected during deposition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…For example, Hiraoka et al (1998) sprayed D atoms over O atoms trapped in an N 2 O matrix at 12 K. The O and D atoms were produced by dissociation of, respectively, N 2 O and D 2 under a dc discharge. Dulieu et al (2010) codeposited O and D atoms produced by dissociating O 2 and D 2 , respectively, onto non-porous amorphous H 2 O ice at 10 K. More recently, Jing et al (2011) deposited D atoms and 18 O (instead of 16 O) at 15-25 K on a synthesized olivine surface. All three groups claimed that D 2 O (HDO) formed during their experiments through surface reactions (1) and (2); however, other O-related species, such as O 2 and O 3 , were also present in or on the samples, and it was difficult to separate information relating to reactions (1) and (2) from the different competing H 2 O-formation channels related to O 2 and O 3 , shown below.…”
Section: H 2 O Formationmentioning
confidence: 99%
“…For example, Hiraoka et al (1998) sprayed D atoms over O atoms trapped in an N 2 O matrix at 12 K. The O and D atoms were produced by dissociation of, respectively, N 2 O and D 2 under a dc discharge. Dulieu et al (2010) codeposited O and D atoms produced by dissociating O 2 and D 2 , respectively, onto non-porous amorphous H 2 O ice at 10 K. More recently, Jing et al (2011) deposited D atoms and 18 O (instead of 16 O) at 15-25 K on a synthesized olivine surface. All three groups claimed that D 2 O (HDO) formed during their experiments through surface reactions (1) and (2); however, other O-related species, such as O 2 and O 3 , were also present in or on the samples, and it was difficult to separate information relating to reactions (1) and (2) from the different competing H 2 O-formation channels related to O 2 and O 3 , shown below.…”
Section: H 2 O Formationmentioning
confidence: 99%
“…These two molecules are thought to be catalyzed by the surface of cold (10−100 K) dust grains composed of silicates or carbonaceous materials. Recently, laboratory experiments have demonstrated that water is easily formed from O atoms (Dulieu et al 2010;Jing et al 2011), but also from O 2 (Oba et al 2009;Ioppolo et al 2010;Chaabouni et al 2012) or even O 3 molecules (Mokrane et al 2009;Romanzin et al 2011) by addition of H atoms. The presence of O, O 2 and O 3 at observable abundances on the surface of grains during ice growth is unlikely because of their high reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…The provenance of asteroidal water has been questioned and the focus of recent literature (11,12); the apparent consensus as yet suggests a continuum (13)(14)(15) of water accretion between anhydrous asteroids and comets and, based in part from analysis of Stardust cometary grains (16), a possible common origin for their water. Water may affect asteroidal petrology post-accretionally (17) with a conversion of anhydrous to hydrous silicates that is sometimes pervasive, as found represented in petrographic grade 1 (C1) CC; in these samples primary silicate minerals and metals are nearly completely replaced by alteration products (18).…”
mentioning
confidence: 99%